Implementation Of E-Government To Improve The Quality Of Public Services In The Border Area Between Indonesia And Timor-Leste - Jando, Emanuel; Andrianus Nani, Paskalis; Paula Bria, Yulianti; D. B. Mau, Sisilia; M. Meolbatak, Emiliana; C. H. Siki, Yovinia; Ngaga, Emerensiana; Ternoiro Alves Santos, Arão; Fernandes Xavier Cham, Marcelo (CV. Inara, 2025)
This community service initiative aims to enhance public service delivery in Weulun Village, a remote border area in East Nusa Tenggara, Indonesia, through the implementation of an e-Government system. Located adjacent to Timor-Leste, Weulun Village faces significant challenges such as limited infrastructure, geographical isolation, and shortages in human resources, which often hinder access to administrative and public services. In response, a participatory and collaborative approach was employed to design and implement a digital public service platform tailored to the village’s specific needs. The process included needs assessment, system planning, capacity building, system testing, and final implementation. The developed web-based system features two user levels: general public and village administrators. It enables digital access to population data, official documents, village profiles, and correspondence services, reducing residents’ dependency on travel to distant government offices. Following system deployment, training and socialization sessions were held to ensure effective use and sustainability. After four months of use, notable improvements were observed in service efficiency, transparency, and community satisfaction. Despite challenges such as limited internet connectivity and hardware constraints, the community’s enthusiasm and adaptability contributed significantly to the program’s success. This project demonstrates the transformative potential of digital technology in improving public service delivery in remote and underserved areas. The successful implementation in Weulun Village offers a model for similar efforts in other Indonesian border villages. Furthermore, this initiative supports the higher education institution’s goals by integrating community engagement with practical learning opportunities for students.